Care as a Fundamental Right: An Urgent Vindication as a Historical Correction Affecting Mainly Women - Saldarriaga-Quintero, Luisa Alejandra; Saldarriaga Grisales, Dora Cecilia; Agudelo-Galeano, Juan Jacobo (Sociedad y Economía, 2025)
In the evolution of Colombian constitutional law, the concept of care has gained relevance by linking fundamental rights with public welfare policies. The jurisprudence of the Constitutional Court and legislative advances have recognized it as essential to guarantee rights such as health, education, pension, equality, non-discrimination and human dignity. This study analyzes, from a jurisprudential line and the Colombian regulatory framework, how care has been configured since the creation of the Constitutional Court, first as a human right and then as a fundamental right. It also examines the co-responsible obligations between family, State and society in order to make visible their implications and transformations.